Respuesta :

Answer:

  • P'(-4, -2)
  • Q'(2, -2)
  • R'(2, -5)

Step-by-step explanation:

Use the given (x, y) coordinates in the transformation formula and simplify.

Transformation

This transformation translates each point right 1 and down 6.

  (x, y) ⇒ (x+1, y-6)

Application

  P(-5, 4) ⇒ P'(-5+1, 4-6) = P'(-4, -2)

  Q(1, 4) ⇒ Q'(1+1, 4-6) = Q'(2, -2)

  R(1, 1) ⇒ R'(1+1, 1-6) = R'(2, -5)

Additional comment

The notation is a bit unconventional. It appears that P' (P prime) is being represented as P^I, which would be interpreted as P with an exponent of I (eye). The "prime" is usually an apostrophe. P' conventionally means the image of point P after some transformation.